Identifying economical and sustainable elements in enhancing the BTS (build then sell) concept for Malaysia housing development - Mohd Noor, Mohd Zairul; Ibrahim, Rahinah (2008)

(untitled)
The awaited anticipation of home ownership by the middle-income group in Malaysia has been marred by the stigma of abandoned housing developments. Abandoned projects are known to cause environmental degradation since most project sites are stripped of their green covers that cause speedier surface water runoffs into drains and streams. Those projects are becoming significant and are further negating the image of the construction industry in the country. The latest solution that was proposed to overcome this problem is the implementation of the Built then Sell (BTS) concept, which was launched by the Prime Minister in 2004. However, the proposal seems not well received by many developers, including the Real Estate and Housing Developers’ Association (REHDA). The purpose of this paper is to develop a theoretical model on how we could address the problem of abandoned housing projects. Through literature survey, we intend to identify key elements in understanding the phenomenon and develop some theoretical point of departures for alleviating this problem through creative financial modeling. We are proposing the inclusion of sustainable elements into the financial model that we believe could provide incentives to housing developers and other stakeholders involved. The paper will compare and analyze existing BTS concepts from the Australia and other country. It will extract the key components and reasoning behind their inclusions so that we can make informed recommendations for BTS implementation in the Malaysian context. The analysis will then guide us in recommending key construct for further integration with the Malaysian Agenda 21 policy. This paper contributes towards the development of a financial model for developing affordable quality housing in Malaysia.